The aromatic carbon-carbon ipso-substitution reaction - Bonesi, Sergio Mauricio (2010)
The aim of this review is to illustrate what we have dubbed an aromatic carbon-carbon ipso-substitution reaction in which a new Ar-C bond is formed at the expense of another Ar-C bond. The potentiality of several C-based leaving groups including alkyl, carbinol, CN, COOH, and carbonyl groups in arylation reactions will be illustrated accordingly for the preparation of biphenyl-, vinyl-, alkynyl-, and alkyl-substituted aromatics. Getting the bond back together: The strategies are unveiled for an aromatic C-C ipso-substitution reaction. This process allows for the one-pot cleavage of Ar-C bonds (e.g., in alkyl and acyl (hetero)aromatics, in benzonitriles, in α,α- disubstituted arylmethanols, and in carboxylic acids) for the formation of a new Ar-C bond (see picture).